2018
DOI: 10.1017/rdc.2018.76
|View full text |Cite
|
Sign up to set email alerts
|

Jericho and the Chronology of Palestine in the Early Bronze Age: a Radiometric Re-Assessment

Abstract: The absolute chronology of Early Bronze Age in the Levant has been the object of a major revision (Regev et al. 2012a), which implied an increase of at least two centuries in respect of traditional chronology. Such a shift back was based upon two sites (Tel Yarmouth, Megiddo) which were the backbone of the “reform,” but actually do not offer complete sequences for the whole EBA. This was the weakest stone of the revision, together with a partial understanding of stratigraphy/contexts from where samples were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This early date supports and complements the "high" absolute chronology for the EB-III period in the southern Levant (Regev et al 2012b). For a different opinion see Nigro et al (2019). The KANE IBA dates show that in this region, the IBA material culture appeared just after, or in parallel with the final decline of the previous EB-III urban culture, around 2500 BC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This early date supports and complements the "high" absolute chronology for the EB-III period in the southern Levant (Regev et al 2012b). For a different opinion see Nigro et al (2019). The KANE IBA dates show that in this region, the IBA material culture appeared just after, or in parallel with the final decline of the previous EB-III urban culture, around 2500 BC.…”
Section: Discussionsupporting
confidence: 67%
“…This research demonstrated that the absolute dating for the end of the EB-III urban culture is around 2500 BC and not around 2300 BC, as was widely assumed for the end of the EB-III and the start of the following period IBA (Mazar 1990;de Miroschedji 2009). The traditional dating of the boundary between EB-III and IBA to around 2300 BC was recently advocated by Nigro (Nigro et al 2019) based on modeling radiocarbon ( 14 C) dates from Jericho, where both those periods were excavated. If the previous EB-III urban culture indeed declined around 2500 BC, we should expect no cultural vacuum, and hence expect to find IBA absolute dates close to 2500 BC.…”
Section: Introductionmentioning
confidence: 99%
“…The site it is strategically located in the modern Tell es-Sultan in the Jordan Valley, Palestine, just north of the Dead Sea. It is one of the best-known site in the Middle East because of its ancient evidence of human occupation (for some scholars, the most ancient in the world) [14,15]. The site has been excavated several times and revealed a sequence of multiple occupation layers (stratum) [14,15].…”
Section: Archaeological Backgroundmentioning
confidence: 99%
“…It is one of the best-known site in the Middle East because of its ancient evidence of human occupation (for some scholars, the most ancient in the world) [14,15]. The site has been excavated several times and revealed a sequence of multiple occupation layers (stratum) [14,15]. Nigro and Hamdan Taha, and Jehad Yasine, since 2015 [14,15].…”
Section: Archaeological Backgroundmentioning
confidence: 99%
“…Such observation extends the duration of the IBA period from about 300 years, as was the previous consensus, to about 500-600 years (Regev et al 2012(Regev et al , 2014Höflmayer et al 2014), shifting more attention to the transition from the EB III to the IBA. Yet another current view is that the end of the EB III did not happen simultaneously everywhere and that there are cases, as in Jericho, where EB III ended later, around 2300 BCE (Nigro et al 2019). Early IBA absolute radiocarbon ( 14 C) dates from around 2500 BCE or even somewhat earlier have been published lately from short-lived samples from Tell Abu el-Niaj in Transjordan (Falconer and Fall 2019;Fall et al 2020) and Khirbat el-'Alya in the Judean Shefelah region (Lev et al 2020).…”
Section: Introductionmentioning
confidence: 99%